The complete chloroplast genome sequence of Fagus sylvatica L. (Fagaceae). Issue 1 (2nd January 2019) - Mader, Malte; Liesebach, Heike; Liesebach, Mirko; Kersten, Birgit
Abstract: The European beech ( Fagus sylvatica ) is one of the most important and widespread tree species in Central Europe and is widely managed for its valuable hard wood. We assembled and characterized the complete chloroplast genome of F. sylvatica to serve as a valuable resource in future genetic studies. The complete plastome sequence is 158, 462 bp in length and contains 131 genes including 83 protein-coding genes, 40 tRNA genes, and 8 rRNA genes. A phylogenetic analysis of 21 Fagaceae plastome sequences shows that the three available Fagus sequences form a cluster, suggesting that the genus Fagus represents a monophyletic clade within the Fagaceae.